Estratégias, recursos e serviços para o ensino e aprendizagem de estudantes com baixa visão nos anos finais do ensino fundamental - Bispo, Beatriz Alves de Deus (2025)
Students with visual impairment (VI) require the use of different teaching strategies, resources and services to access content, according to their abilities and needs, in addition to generally needing more time to carry out classroom activities. They have the right to receive all the educational support necessary for their learning to be effective. Based on this, the objective of this study was to analyze the strategies, teaching resources used and services offered to students with low vision enrolled in the final years of elementary school, from the perspective of the students themselves, their Special Education teachers and regular classroom teachers. This is a descriptive study, in which data collection took place through semi-structured interviews. The data obtained were transcribed and subjected to content analysis, interpreted and organized into categories according to the participants' statements. Information was obtained from students with visual impairment and their regular classroom and special education teachers about the strategies and resources used, such as delivery of expanded activities, adaptation of activities, development of mind maps, use of cell phones to take photos of the board and enlarge them, use of notebooks with enlarged and darker lines, numbering of lines for better location during writing and also what services are offered to students with visual impairment in public schools. It was noted that students with low vision have different demands, abilities and difficulties and that under no circumstances should a ready-made recipe of strategies and resources be offered, as simply expanding activities is not enough.